Armenia : Increasing Preventive Screening for Non-Communicable Diseases in Armenia - World Bank (World Bank, Washington, DC, 2021)
More people around the world are dying from noncommunicable diseases than ever before. These diseases, which include cancer, chronic respiratory diseases, diabetes, and heart disease, prematurely kill more than 15 million people between ages 30 and 69 each year. Many of these health conditions also make individuals more susceptible to severe forms of other diseases like Coronavirus disease 2019 (COVID-19). This study targeted adults between the ages of 35 and 68 in Armenia who had not been screened in the preceding year. The baseline data suggests this population was not economically secure: half of participants responded that their income was sufficient for basic family needs, such as food, clothing, and utilities, but not enough for big purchases like a car, while 35 percent responded that their income is sufficient for everyday food but not for clothes and other basic needs. More than half of those in the study were unemployed. This research finds that conditional incentives and personalized invitations can substantially increase screening for diabetes and hypertension for those who haven’t been recently screened. Further research may be needed to evaluate these interventions at scale.